(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This paper examines John Rawls’s distinction between the reasonable and the rational within the framework of political liberalism. It argues that a just democratic society depends on fair cooperation, reciprocity, and public reason rather than solely on the pursuit of individual interests. The paper also explores the concepts of reasonable pluralism, comprehensive doctrines, and overlapping consensus, emphasizing their role in securing political stability and legitimacy in constitutional democracies characterized by diverse moral, religious, and philosophical beliefs. This abstract is generated with artificial intelligence.